Analisis Dan Perancangan Sistem Informasi Manajemen Arsip Berbasis Web Pada Sekretariat DPRD Kota Jambi - Latif, Raden Abdul; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2020)
The DPRD Secretariat has issues relating to archiving files, where the files are difficult to find when needed. The DPRD Secretariatstill uses a manual book system to record incoming and outgoing letters. The number of files is increasing everyday, and the manual books system is vulnerable by damaged and vanish, also stand archiving issues of the DPRD Secretariat. This study aims to analyze and design a Web-based prototype in Archive Management Information System on incoming and outgoing mail, through the Unified Modeling Language (UML)system modeling method. This system is featured to manage admin data, user data, and archive data, notifying data, managing reports, sending, receiving and archiving security. The prototype is needed to be develoved and implemented at the Jambi city DPRD Secretariat as a solution to the archiving issues, as well as a step to computerize the archiving DPRD Secretariat.